Sleep duration is reduced in elite athletes following night-time competition - Sargent, C.; Roach, G. D. (Chronobiology International, 2016)
This study examined the impact of competition on the sleep/wake behaviour of elite athletes. The sleep/wake behaviour of Australian Rules Football players was assessed with wrist activity monitors on the night immediately before, and the night immediately after, a day game and an evening game. The time of day that a game occurred had a marked influence on sleep/wake behaviour later that night. After the evening game, sleep onset was later, time in bed was shorter and total sleep obtained was less than after the day game. It is yet to be determined whether a reduction in sleep after evening games impairs recovery.